2021
DOI: 10.3390/antibiotics10121480
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antibacterial Efficacy of Halicin against Pathogenic Bacteria

Abstract: Artificial intelligence (AI) is a new technology that has been employed to screen and discover new drugs. Using AI, an anti-diabetic treatment (Halicin) was nominated and proven to have a unique antibacterial activity against several harmful bacterial strains, including multidrug-resistant bacteria. This study aims to explore the antibacterial effect of halicin and microbial susceptibility using the zone of inhibition and the minimum inhibition concentration (MIC) values while assessing the stability of stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Biofilms complicate the treatment of orthopaedic infections by protecting bacteria from the host immune system and many antibiotics. Halicin was recently found to have potent activity against the planktonic cultures of many bacterial species, including S. aureus [1, 7, 48], and those findings were confirmed in our study. Importantly, halicin was effective against proliferating and quiescent bacteria [48].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Biofilms complicate the treatment of orthopaedic infections by protecting bacteria from the host immune system and many antibiotics. Halicin was recently found to have potent activity against the planktonic cultures of many bacterial species, including S. aureus [1, 7, 48], and those findings were confirmed in our study. Importantly, halicin was effective against proliferating and quiescent bacteria [48].…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation is that our study focused exclusively on a single bacteria type. However, the possible generalizability of our results is supported by previous findings that halicin has potent activity against planktonic forms of many bacterial species, including multidrug-resistant representatives of both gram-positive and gram-negative species [1,7,48]. Nonetheless, future studies should test the effects of halicin on the biofilms of other bacterial species, including multidrugresistant bacteria.…”
Section: Limitationssupporting
confidence: 83%
“… 21 , 22 Halicin also has broad-spectrum activity against planktonic cultures of many Gram-positive and Gram-negative bacteria, including multidrug-resistant clinical isolates. 20 , 37 Halicin is the first completely novel antibiotic identified by deep-learning artificial intelligence approaches. 20 Follow-up studies revealed that halicin has potent broad-spectrum activity, but the antibacterial mechanism of halicin remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors test a new substance previously reported by Stokes et al [8]; figuratively, a computer selected and assembled this very innovative and promising antibiotic, halicin, from many substances that exploit the weaknesses in bacterial defenses. Halicin is the first of a new generation of antibiotics, and although it has not yet been tested in patients, new perspectives are opening up for better treatment of patients with biofilm infections and multidrug-resistant pathogens [2]. Next steps might seek to exploit recent successes in biofilm research to develop next-generation antibiotics, to better simulate in vitro the effects of antibiotics on bacteria and biofilms under laboratory conditions.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%